(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
: This article talks about the military tactics of Amir Temur, also known as Temur, a great general of the 14th century. His work on the military front had a significant impact on world military art. The article examines the main elements of Amir Temur’s military tactics, including his organizational skills, efficient use of mobility, psychological warfare, and new combat formations. Through historical analysis, the research shows Timur’s contribution to the development of military strategy, which was later recognized and accepted by other famous generals